Case report: COVID-19 infection in a pregnant 33-year-old kidney transplant recipient - Supák, Dorina; Mészáros, Balázs; Nagy, Márta; Gáspár, Dániel; Wagner, László J.; Kukor, Zoltán; Valent, Sándor (Frontiers in Medicine, 2022)
Patients facing SARS-CoV-2 infection with comorbidities, especially patients whose immune system is weakened have higher chances to face severe outcomes. One of the main reasons behind the suppression of the immune system is iatrogenic, in patients who have autoimmune diseases and/or had an organ transplanted. Although there are studies which are examining immunocompromised and/or transplanted patients with COVID-19 infection, furthermore there is a limited number of studies available which are dealing with COVID-19 in pregnant women, however it is unique and is worth reporting when these factors are coexisting. In this study we present the case of a 33-year-old Caucasian pregnant woman, who had a kidney transplant in 2009 and contracted SARS-CoV-2 virus on the 26th gestational week, in 2021. After her infection, superimposed preeclampsia was diagnosed and due to the worsening flowmetric parameters she gave birth to a premature male newborn with cesarean section. Our kidney transplant patient’s case highlights how COVID-19 disease can lead to preeclampsia and artificial termination of gestation.